Cradles of Complexity: Bicornuate uterus and its pregnancy outcomes - Jagathiswari, P.S.; Rajalekshmi, Rajalekshmi; Christable, Evangeline (Journal of Neonatal Surgery, 2025)
This case series examines pregnancy outcomes in three women with bicornuate uterus, a congenital uterine anomaly resulting from incomplete Müllerian duct fusion. All cases resulted in preterm deliveries (34-37 weeks), with two requiring cerclage for cervical incompetence and all delivering via cesarean section for malpresentation or fetal distress. Two pregnancies developed intrauterine growth restriction, while one twin gestation was complicated by placenta previa. Neonatal outcomes varied from significant respiratory morbidity in a 34-week delivery to minimal complications in a 36-week twin delivery. These cases demonstrate the characteristic obstetric challenges of bicornuate uterus, including preterm birth (100% incidence in our series), cervical insufficiency (66%), and abnormal placentation (33%). Despite these complications, all pregnancies achieved live births through multidisciplinary care involving serial ultrasound monitoring, individualized cerclage placement, and planned cesarean delivery. The series highlights the importance of early anomaly diagnosis, specialized antenatal surveillance, and delivery planning at tertiary centers. While bicornuate uterus significantly impacts pregnancy outcomes, these cases illustrate that favorable results are attainable with vigilant, tailored management addressing the specific risks of this uterine anomaly.